Rancang Bangun Media Pembelajaran Interaktif Mata Pelajaran Penerapan Rangkaian Elektronika menggunakan Articulate Storyline - Syifa Ananda, Rahma Dhini; Anori, Sartika (MASALIQ, 2025)
This study aims to design and develop valid and practical interactive learning media using Articulate Storyline software for the topic “Digital Circuits” for Grade XI students of Industrial Electronics Engineering at SMK Negeri 5 Padang. The background of this research is the need for learning media that can optimally facilitate the learning process, enabling students to understand concepts independently and contextually. The researcher employed the 4-D development model, which includes the Define, Design, Develop, and Disseminate stages. The media's validity was assessed by two subject matter experts with a cumulative score of 92.87% and two media experts with a score of 94.79%, both categorized as “very valid.” Practicality testing was conducted with 20 students and obtained a score of 96.52%, categorized as “very practical.” These results indicate that learning media based on Articulate Storyline is suitable for use as a learning aid in the Digital Circuits instructional process. These findings offer practical contributions to the development of interactive digital learning media and support the enhancement of vocational education quality, particularly in the electronics competency area.